Terminal sterilization: Conventional methods versus emerging cold atmospheric pressure plasma technology for non‐viable biological tissues. Issue 7 (15th December 2016) - Marsit, Nagi M.; Sidney, Laura E.; Branch, Matthew J.; Wilson, Samantha L.; Hopkinson, Andrew
Abstract : Tissue products are susceptible to microbial contamination from different sources, which may cause disease transmission upon transplantation. Terminal sterilization using gamma radiation, electron‐beam, and ethylene oxide protocols are well‐established and accepted, however, such methods have known disadvantages associated with compromised tissue integrity, functionality, safety, complex logistics, availability, and cost. Non‐thermal (cold) atmospheric pressure plasma (CAP) is an emerging technology that has several biomedical applications including sterilization of tissues, and the potential to surpass current terminal sterilization techniques. This review discusses the limitations of conventional terminal sterilization technologies for biological materials, and highlights the benefits of utilizing CAP. Abstract : This review discusses the challenges surrounding terminal sterilization of tissues and biological transplant materials. The limitations of conventional terminal sterilization techniques of biological materials are identified, particularly the damage caused to tissue structure, and the benefits of using non‐thermal (cold) atmospheric pressure plasma in terminal sterilization of soft thin tissues and biomaterial constructs discussed.